A critical narrative questioning the assessment of physical literacy: foster authentic human flourishing across the life course - Huang, Yan (Frontiers in Sports and Active Living, 2024)
The study provides a summary, reflection, and clarification on the existing literature amid the recent rise in physical literacy assessment through a critical narrative that will contribute to future developments. In this review, the author addressed the significance of acknowledging the ultimate goal of assessing physical literacy throughout the life course is to foster authentic human flourishing. The study questioned the assessment practice in detail by discussing whether it is to translate and validate or to establish locally and to quantify or to specify qualitatively. The current tendency of a comprehensive dimension but not an inclusive journey was found. Subject to limitation, the merits of this study still stand and, moreover, further point to valuable areas for further inquiry that may refine and foster physical literacy and authentic human flourishing across the life course. And based on the arguments, future direction and recommendations when conducting assessment were discussed.